BIO-ECONOMIC APPROACH ON ASSESSING MANAGEMENT OPTIONS FOR THE FISHERY: The Case of Open Water Fishery of South Sumatra, lndonesia - Sonny Koeshendrajana; Oscar Cacho (Research Center for Fisheries, 2001)
The issue of better management for tropical inland fisheries has become one of the major problems for Indonesia. For the decision-makers, the question of to whom to assign property rights is difficult because it involves an assessment of who can use the resource in the best interests of society.